2014
DOI: 10.1080/15459624.2014.935781
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure Assessment of Highway Toll Station Workers to Vehicle Engine Exhaust

Abstract: Toll station workers are occupationally exposed to vehicle engine exhaust, a complex mixture of different chemical substances, including carcinogenic compounds. Therefore, a study was carried out on attendants of two highway toll stations to describe their occupational exposure to vehicle engine exhaust, based on a worst-case scenario approach. Personal sampling was conducted during the day shift for all attendants, testing for three groups of chemical substances: polycyclic aromatic hydrocarbons (PAHs), volat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The major pathogenic microbes that could be transmitted through occupational exposure include human immunodeficiency virus, hepatitis B virus, hepatitis C virus and treponema pallidum (Wang et al, 2020). In addition, several viral epidemics have occurred in the past 20 years, such as severe acute respiratory syndrome, H1N1 influenza, Middle East respiratory syndrome, Ebola virus disease and coronavirus disease 2019 (COVID‐19), which have seriously threatened the health and safety of health care workers (Belloc‐Santaliestra et al, 2015; Descatha & Roquelaure, 2018; Wang et al, 2015). A study indicated that more than 890 health care workers were infected, with a mortality rate of 57%, during the Ebola virus outbreak in sub‐Saharan Africa (Ngatu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major pathogenic microbes that could be transmitted through occupational exposure include human immunodeficiency virus, hepatitis B virus, hepatitis C virus and treponema pallidum (Wang et al, 2020). In addition, several viral epidemics have occurred in the past 20 years, such as severe acute respiratory syndrome, H1N1 influenza, Middle East respiratory syndrome, Ebola virus disease and coronavirus disease 2019 (COVID‐19), which have seriously threatened the health and safety of health care workers (Belloc‐Santaliestra et al, 2015; Descatha & Roquelaure, 2018; Wang et al, 2015). A study indicated that more than 890 health care workers were infected, with a mortality rate of 57%, during the Ebola virus outbreak in sub‐Saharan Africa (Ngatu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Occupational exposure has aroused widespread concern in various professions and has become one of the most serious public health issues worldwide (Belloc-Santaliestra et al, 2015;Descatha & Roquelaure, 2018;Wang et al, 2015). Health care workers provide patient care in environments that are considered to be one of the most unsafe occupational settings (Mossburg et al, 2019).…”
mentioning
confidence: 99%
“…As regard to the industrial scenarios, [75][76][77][78][79][80][81][82][83][84] airborne formaldehyde is generally present at low levels (micrograms), except where it is directly released from resins 76 or used for its biocidal properties in dairy facilities 76,81 and fish hatcheries. 83 In addition to the well-known exposure profile of firefighters, [85][86][87] other investigated scenarios are very diversified, both in terms of settings (school campuses, laundries, copy centers etc) [88][89][90][91][92][93][94] and in terms of formaldehyde levels (from not detectable to some mg m −3 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the well‐known exposure profile of firefighters, 85 , 86 , 87 other investigated scenarios are very diversified, both in terms of settings (school campuses, laundries, copy centers etc) 88 , 89 , 90 , 91 , 92 , 93 , 94 and in terms of formaldehyde levels (from not detectable to some mg m −3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation